2009
DOI: 10.1007/s11859-009-0415-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison study of chitosan/β-cyclodextrin and carboxymethyl chitosan/β-cyclodextrin microspheres

Abstract: To compare two microspheres of chitosan/β-cyclodextrin and carboxymethyl chitosan/β-cyclodextrin loaded theophylline as pulmonary sustained drug delivery carriers, the characteristics and ciliotoxicity were studied. The drug loadings of chitosan/ β-cyclodextrin and carboxymethyl chitosan/β-cyclodextrin microspheres were 21.09% and 21.42%, and the encapsulation efficiencies were 91.40% and 92.80%. The distributions of 50% (d 0.5 ) of chitosan/β-cyclodextrin and carboxymethyl chitosan/β-cyclodextrin microspheres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Studies on the characteristics and ciliotoxicity of these systems evidenced an high drug loading and encapsulation effi ciency and suggested that them should be eff ective as for sustained pulmonary drug carriers [49].…”
Section: Cyclodextrins As Molecular Recognition Elementsmentioning
confidence: 99%
“…Studies on the characteristics and ciliotoxicity of these systems evidenced an high drug loading and encapsulation effi ciency and suggested that them should be eff ective as for sustained pulmonary drug carriers [49].…”
Section: Cyclodextrins As Molecular Recognition Elementsmentioning
confidence: 99%